PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Mahendra Dj, Alfredo; Sri Artini, Luh Gede; Suarjaya, A.A Gede (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 6 Nomor 2 Tahun 2012, 2012)
Firm value is very important because the high value of the firm which will be followed by higher shareholder wealth. This study aims to determine the effect on the value of the company’s financial performance with the dividend policy as a moderating variable. The population in this study are all manufacturing companies listed on the BEI consecutive dividend during the period 2006-2009. The results showed that: 1) liquidity not significant positive effect on firm value, 2) dividend policy is not able to significantly moderate the effect of liquidity on the value company, 3) leverage not significant negative effect on firm value, 4) dividend policy is not able to significantly moderate the effect of leverage on firm value, 5) Profitability significant positive effect on firm value, 6) dividend policy is notable to significantly moderate the effect of profitability on firm value
Keywords: Financial Performance, Firm value, Dividend Policy